2022
DOI: 10.1039/d2ce00508e
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxies of Ca-sulfates on calcite (CaCO3) I. Gypsum {010} on the calcite {10.4} form: epi-twins of gypsum induced by the calcite substrate

Abstract: 3D-epitaxy of the {010} pinacoid of deposited gypsum (CaSO4·2H2O) on the substrate {10.4} calcite rhombohedron is described, in order to give a theoretical background to the replacement of calcite by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Further, swallow-tail twins do theoretically occur in all three cases of the epitaxies of bassanite on (10.4) Cc . In brief, these new 2D twin laws have been found for bassanite, promoted by the calcite substrate; together with the (10.4) Cc / (010) Gypsum coupling examined earlier (Aquilano et al, 2022), a new way of thinking is being developed in detail about the epitaxy between different species. This can be particularly useful when a new mineralogical species tends to replace another, as in the case of Ca sulfates (gypsum, bassanite, anhydrite) replacing calcite, in nature and/or the laboratory (Ruiz-Agudo et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Further, swallow-tail twins do theoretically occur in all three cases of the epitaxies of bassanite on (10.4) Cc . In brief, these new 2D twin laws have been found for bassanite, promoted by the calcite substrate; together with the (10.4) Cc / (010) Gypsum coupling examined earlier (Aquilano et al, 2022), a new way of thinking is being developed in detail about the epitaxy between different species. This can be particularly useful when a new mineralogical species tends to replace another, as in the case of Ca sulfates (gypsum, bassanite, anhydrite) replacing calcite, in nature and/or the laboratory (Ruiz-Agudo et al, 2016).…”
Section: Discussionmentioning
confidence: 85%
“…We recently investigated all compatible 3D and 2D lattice coincidences (herein 3D-and/or 2D-LCs) that can occur at the interface between the {10.4} form of cleaved calcite (substrate) and the {010} pinacoid of gypsum (deposit) (Aquilano et al, 2022). Working on calcium sulfates deposited on gypsum, we knew that when gypsum is heated above $150 C in the dry state (or at 75 C in methanol-water solutions), a part of the crystalline water is removed and CaSO 4 Á0.5H 2 O is formed (Maslyk et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…the interaction energy between the atoms contained in the d 10.4 slice, and found that E 10:4 slice = 0.222 erg  10 À10 ion À1 corresponds to 94.32% of the calcite total crystallization energy. The shape of growth (or dissolution) of {10.4} patterns (spirals and/or 2D nuclei) is theoretically limited (Aquilano et al, 2022a) by the dominant border steps h441i, followed by the h421i vertical and h010i horizontal directions, as can be appreciated in Fig. 1.…”
Section: A Short Summary Of the {104} Surfaces Of Calcitementioning
confidence: 96%
“…An epitaxial relationship between the {010} pinacoid of gypsum and the {10.4} rhombohedron of calcite (Ruiz-Agudo et al, 2016;Aquilano et al, 2022) has been demonstrated. Therefore, the effect of carbonate anions -ubiquitous in evaporitic environments -on the habit of gypsum crystals deserves further investigation.…”
Section: Introductionmentioning
confidence: 96%